A Critique of the Smooth Inverse Frequency Sentence Embeddings (Student Abstract) - Karipbayeva, Aidana; Sorokina, Alena; Assylbekov, Zhenisbek (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
We critically review the smooth inverse frequency sentence embedding method of Arora, Liang, and Ma (2017), and show inconsistencies in its setup, derivation and evaluation.